Utilization of grafting technique for sustaining cantaloupe productivity and quality under deficit irrigation water - Ezzo, M. I. (2021)
The results showed that moderate irrigation level (75% ETc) increased the early yield, fruits number, by 15.3 and 17.4%, respectively, compared to control irrigation treatment (100% ETc). No significant variation was found concerning total yield between 100 and 75% ETc, so this led to an increase in WUE of moderate irrigation level (75% ETc) by 34.3%, compared to control irrigation treatment (100% ETc). Increasing deficit levels up to 50% ETc reduced the total yield by 47.4%, but it increased the WUE by 8.8%, compared to the non-deficit irrigation level (100% ETc). Meanwhile, grafting both cultivars on Cobalt rootstock improved the fruit number, total yield, and WUE by 39.2%, 26.9%, and 24.1%, respectively when irrigated with the moderate irrigation level (75% ETc), as compared to the non-grafted plants which recorded the highest decrease when irrigated with deficit irrigation level (50% ETc).